2020
DOI: 10.1002/ijgo.13405
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between single versus dual trigger for poor responders in GnRH‐antagonist ICSI cycles: A randomized controlled study

Abstract: Objective To investigate whether dual triggering of final oocyte maturation with a combination of gonadotropin‐releasing hormone (GnRH) agonist and human chorionic gonadotropin (hCG) can improve the number of retrieved oocytes and clinical pregnancy rate in poor responders undergoing in vitro fertilization/intracytoplasmic sperm injection (IVF‐ICSI) cycles using a GnRH‐antagonist protocol. Methods A randomized controlled trial included poor ovarian responders indicated for ICSI using a GnRH‐antagonist protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…In addition, it is important to note that both study groups exceeded expectations for both CPR and LBR compared with our center’s overall success rate in women <35 years old undergoing fresh autologous ET. This finding correlates with multiple research studies that showed that dual trigger improves IVF outcomes ( 38 , 39 , 40 , 41 , 42 , 43 ). Included in these studies was a double-blind, randomized, controlled trial that showed that the use of dual trigger had a significantly higher number of M2 oocytes retrieved, CPR, and LBR compared with those of hCG only trigger ( 40 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, it is important to note that both study groups exceeded expectations for both CPR and LBR compared with our center’s overall success rate in women <35 years old undergoing fresh autologous ET. This finding correlates with multiple research studies that showed that dual trigger improves IVF outcomes ( 38 , 39 , 40 , 41 , 42 , 43 ). Included in these studies was a double-blind, randomized, controlled trial that showed that the use of dual trigger had a significantly higher number of M2 oocytes retrieved, CPR, and LBR compared with those of hCG only trigger ( 40 ).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, it is important to note that both study groups exceeded expectations for both CPR and LBR compared with our center's overall success rate in women <35 years old undergoing fresh autologous ET. This finding correlates with multiple research studies that showed that dual trigger improves IVF outcomes (38)(39)(40)(41)(42)(43). Included in these studies was TABLE 2 Clinical characteristics of cycles that did and did not achieve a live birth.…”
Section: Discussionsupporting
confidence: 74%
“…The full text of 21 of the 25 remaining articles was reviewed (four were not retrieved). Six articles were included (Schachter et al, 2008;Kim et al, 2014;Decleer et al, 2014;Mahajan et al, 2016;Maged et al, 2021;Haas et al, 2020) in quantitative or meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…Table 4 shows the drugs and dosages used in the different studies for COH (total dose of FSH administered was cited in half of the studies) and the trigger protocol; all used hCG as the conventional trigger. Two studies used 250 µg / 6500 IU of hCG (equivalent total dose); two studies used a higher dose of 10,000 IU of hCG (Maged et al, 2021;Haas et al, 2020); and two studies (Schachter et al, 2008;Decleer et al, 2014) used a dosage of 5000 IU, which was lower than the dose used in the rest of the studies. Kim et al (2014) was the only study in which placebo was added to the conventional hCG trigger.…”
Section: Controlled Ovarian Hyperstimulation Regimensmentioning
confidence: 99%
“…13 There are meagre number of studies in literature evaluating the effects of dual triggering on IVF outcomes in various subgroups of patients such as hyper-responder, normo-responder or poor-responder women. 5,6,11,[14][15][16][17][18][19][20][21][22][23][24][25] Furthermore, studies reporting live birth rates, the ultimate goal of infertility treatment, in dually triggered women with expected normal ovarian response are even scarcer. 5,6,11,21,23,25 Therefore, current amount of evidence is not adequate to recommend or argue against the use of dual triggering particularly in women with predicted normal ovarian response.…”
mentioning
confidence: 99%